Odpowiedzi

Najlepsza Odpowiedź!
2010-03-17T22:38:35+01:00
A) R = ax kreska ułamkowa b
b) y = 2t - 3x
c) y = 2(x-1)
d) y = x-1 kreska ułamkowa 2
e) y = 2 kreska ułamkowa x-1
f) P = jedna trzecia (a do kwadratu + 2ax)


a) R=a+xkreska b |×b
R×b= a+x | - a
x= R×b-a

b) y=2t-3x |+3x
y+3x= 2t | - y
3x=2t-y | ÷3
x= 2t-y pod kreska 3

c) y= 2(x-1)
y= 2x-2 | +2
2x= y+2 | ÷2
x= y+2 pod kreska 2

d)y = x-1 pod kreska 2 |×2
2y=x-1 | +1
x= 2y+1

e)y = 2 pod kreska x-1 |× x-1
y×x-1 =2 |+1
y×x=3 |÷y
x=3 pod kreska y

11 3 11